Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Nganjuk - Sulistyowati, Yayuk; Laely, Nur; Utami, Sasi (MARGIN ECO, 2024)
This study aims to determine work motivation and discipline's effect on employee performance in the Nganjuk sub-district office. This type of research uses descriptive quantitative with a survey approach where the questionnaire will be distributed to all research respondents, where the population in this study is all employees in the Nganjuk sub-district office, totaling 55 people. In determining the sample used saturated sampling where the entire population is used as a respondent considering the population is less than 100. Multiple regression analysis is used to test the results of the respondent's data to measure the effect of the dependent variable on the independent variable. The test results show that, simultaneously or partially, work motivation and work discipline have a significant effect on employee performance at the Nganjuk sub-district office